We are tasked to solve the value of p(8a) in the expression p(x)=3x^2-4.
This means that what would find the value of the expression when x=8a. To solve this, we simply substitute the value of x in the expression.
p(x)=3x^2-4
p(8a)=3(8a)^2-4
p(8a)=3(64a^2)-4
p(8a)=192a^2-4
Answer:
1) y = 2(x+3)^2 -4
2) x+6/x-4
3) 2x^2 + 6x +20 = 0
Step-by-step explanation:
Answer:
W'' = (2, -3)
Step-by-step explanation:
Reflection over the x-axis negates the y-coordinate and leaves the x-coordinate alone. The W becomes ...
... W' = (-2, -3)
Reflection over the y-axis negates the x-coordinate and leaves the y-coordinate alone. The W' becomes ...
... W'' = (2, -3)